2018
DOI: 10.1002/slct.201803034
|View full text |Cite
|
Sign up to set email alerts
|

Disposed Dry Cells as Sustainable Source for Generation of Few Layers of Graphene and Manganese Oxide for Solid‐State Symmetric and Asymmetric Supercapacitor Applications

Abstract: Recycling electronic wastes (e‐wastes) is one of the steps to build greener and cleaner environment. In this work, re‐using of disposed dry cell (zinc‐carbon battery) components to generate graphene and manganese oxide for energy storage application has been demonstrated. The obtained materials have been characterized by X‐ray diffraction, Fourier transformed infrared spectroscopy, Raman spectroscopy and scanning electron microscope. The electrochemical performances of the generated graphene and the MnO2 have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…A supercapacitor may last up to 80,000 cycles, depending on temperature and voltage load [49,50]. Nanotechnology must improve high-capacity capacitors' electrical storage capability to compete with batteries.…”
Section: Supercapacitormentioning
confidence: 99%
“…A supercapacitor may last up to 80,000 cycles, depending on temperature and voltage load [49,50]. Nanotechnology must improve high-capacity capacitors' electrical storage capability to compete with batteries.…”
Section: Supercapacitormentioning
confidence: 99%
“…Its broad potential window and good specic capacitance allow absorbing more ions from the electrolyte. [64][65][66][67] Furthermore, based on the above CV and CP results, Co 3 O 4 @MnO 2 -3 is assigned as a positive electrode for the two electrode systems. The operating potential window for the two electrode systems of Co 3 O 4 @MnO 2 -3//AC is performed by combining both electrodes.…”
Section: Electrochemical Performancementioning
confidence: 99%
“…Owing to the favourable characteristics like higher surface to volume ratio, enriched surface area, superior concentration of edge atoms, quantum confinement effect, easy solubility in non-aqueous and aqueous solvents, functionalization and easy doping conditions, Quantum Dots (QDs) are been considered for various range of applications like photovoltaics, bio-sensing, light-emitting diodes, bio-imaging, batteries, fuel cells etc. [10,11]. Moreover, research findings have also shown their viability in coalescing with other nanomaterials to develop better workable composites for application purposes.…”
Section: Introductionmentioning
confidence: 97%